ORAL CAVITY, AFT, MATHEMATICAL MODEL, BIOFILM, MICROORGANISMS, DYNAMIC MODEL (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The process of antiplaque in the oral cavity (AFT), i.e. the accumulation of microorganisms and the formation of biofilm in the oral cavity, is of great importance in the fields of dentistry and oral hygiene. This article presents the key literature and online resources needed to develop a mathematical model of the process of having AFT in the oral cavity. This model helps us understand the convergence of microorganisms, the formation of biofilm and their dynamics.